Effects of Micronutrients on the Growth and Phytochemical Composition of Basil (Ocimum basilicum L.) in the Field and Greenhouse (Hydroponics and Soil Culture) - Hamid Aghamirzaei; Hasan Mumivand; Abdollah Ehtesham Nia; Mohamad Reza Raji; Alfred Maroyi; Filippo Maggi (Plants, 2024)
The current research was conducted to compare the growth, yield, and phytochemical composition of basil (Ocimum basilicum) in the open field and the soil and hydroponic cultivation in a greenhouse. Furthermore, the effect of foliar spraying of micronutrients on this crop was also evaluated. In each of the cultivation systems, foliar spraying of one micronutrient, either iron sulfate (Fe), zinc sulfate (Zn), copper sulfate (Cu), manganese sulfate (Mn), or boric acid (B), at a concentration of 0.1% was applied in a randomized complete block design. Plants grown in the hydroponic system had higher yield and biomass. The concentration of the elements K, Ca, Mg, N, P, Mn, Fe, B, and Zn in the leaves of hydroponic plants was higher. Contrarily, plants cultivated in the field showed higher stem dry weight, essential oil content, phenolic and flavonoid content, and antioxidant activity. The level of methyl chavicol was higher in the hydroponic culture, but the level of 1,8-cineole was much lower in this cropping system. Foliar spraying of Cu, Mn, Zn, Fe, or B significantly increased leaf dry weight and anthocyanin content. In field conditions, the highest levels of phenolics, flavonoids, and antioxidant capacity were observed with Zn or Mn application. In the hydroponic system, foliar spraying of Zn or B led to the highest antioxidant capacity, and total phenolic and flavonoid contents. Overall, the basil plants cultivated in the field showed higher bioactive ingredients. However, the essential oil of plants cultivated in the hydroponic system had a higher economic value due to its higher percentage of methyl chavicol.